Pengaruh Persepsi Kemudahan Penggunaan dan Manfaat Terhadap Minat Penggunaan E-Wallet Pada Mahasiswa Universitas Muhammadiyah Riau - Algusri, Jeki; Magdalena, Maria; Misral, Misral; Karimi, Kasman; Diva Darmawani, Rengganis (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This quantitative study was conducted to understand the impact of the ease of use of E-Wallets and their benefits on the university students at Muhammadiyah Riau. The research population consists of active faculty members at Universitas Muhammadiyah Riau. Data were collected using SPSS version 22, which understands and uses electronic currency cards. This study uses a simple, acak sampling technique by sending questionnaires to potential respondents. In this research, the technique of data analysis used is called regression linear berganda analysis. This study indicates that people's perceptions about the ease of use and benefits of the product have a positive and significant impact on their desire to use it. Electronic Wallet.